2018
DOI: 10.3390/s18072186
|View full text |Cite
|
Sign up to set email alerts
|

An Outlier Detection Method Based on Mahalanobis Distance for Source Localization

Abstract: This paper addresses the problem of localization accuracy degradation caused by outliers of the angle of arrival (AOA). The problem of outlier detection of the AOA is converted into the detection of the estimated source position sets, which are obtained by the proposed division and greedy replacement method. The Mahalanobis distance based on robust mean and covariance matrix estimation method is then introduced to identify the outliers from the position sets. Finally, the weighted least squares method based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…It was demonstrated in [11] that the Sobol' sensitivity indices can be obtained from the expansion coefficients in (5) and (6). These sensitivity indices translate how each of the input variables of the problem contributes to the output uncertainty.…”
Section: B Polynomial Chaos Expansions Of the Positionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated in [11] that the Sobol' sensitivity indices can be obtained from the expansion coefficients in (5) and (6). These sensitivity indices translate how each of the input variables of the problem contributes to the output uncertainty.…”
Section: B Polynomial Chaos Expansions Of the Positionmentioning
confidence: 99%
“…Anchor selection for AoA localization in the literature mostly concerns acoustic sensors [5], and do not rely on the uncertainty of AoA measurements. Instead, methods of outlier detection that are able to detect if one of the measurements is strongly biased are proposed [6]. In fact the uncertainty on the AoA measurement can be modelled as a sum of two effects: the measurement noise, which can be modelled as a Gaussian distribution around the true AoA, and outlier measurements which can be modelled as a Uniform distributed random variable [7].…”
Section: Introductionmentioning
confidence: 99%
“…calization that acquires merely the one-dimensional bearing measurements as AOA observations [8]- [10]. Depending on how the error-prone data are treated, these methods can be roughly divided into the robust statistics/outlier detection [8], [9] and expectation maximization [10] ones. In the general 3-D setting of the localization system, mitigating the bias errors in both azimuth and elevation angle measurements has been considered by the authors of [4] and [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that they exhibit a good consistency when the estimation error of each individual sensor follows a Gaussian distribution. However, sensor failures, data loss, NLOS propagation or unexpected interference may impose uncertainty on sensor networks which result in the presence of unreliable measurements [16,17].…”
Section: Introductionmentioning
confidence: 99%